The genus Liljeborgia in the Mediterranean Sea, with the description of a new species (Crustacea: Amphipoda: Liljeborgiidae) - D'acoz, Cédric D'udekem (Zootaxa, 2012)
A new amphipod crustacean, Liljeborgia clytaemnestra sp. nov., is described based on specimens from Malta andthe Bay of Naples. It is quite similar to the sympatric L. dellavallei Stebbing, 1906, but it has narrower and moreregular-sized spines on the propodus of pereiopods 3–4. The longest spine on the dorsolateral border of the pedun-cle of uropod 1 is not strongly elongate in adult males, as in L. dellavallei. The apical spines on the lobes of the tel-son are much longer than in L. dellavallei. L. clytaemnestra sp. nov. is actually more similar to two northeasternAtlantic species, the British L. pallida (Spence Bate, 1857) and the Scandinavian L. brevicornis (Bruzelius, 1859)than to the Mediterranean L. dellavallei. In L. clytaemnestra sp. nov., article 2 of the mandibular palp has setae ondistal third, whilst setae are restricted to tip in the two other species. Article 3 of the mandibular palp is also longerin L. clytaemnestra sp. nov. than in the two Atlantic species. The spines of the outer plate of the maxilliped are lon-ger in L. clytaemnestra sp. nov. than in the two other species. The most distal spine of the propodus of pereiopods3–4 is reduced in L. clytaemnestra sp. nov. and L. brevicornis, but not in L. pallida. The serration of the posteriorborder of the basis of pereiopod 7 is much stronger in L. clytaemnestra sp. nov. than in the two other species.Finally, in L. clytaemnestra sp. nov., the spines of the lobes of the telson are longer than in L. pallida. A lectotypeis designated for L. dellavallei. The presence/absence of a posterodorsal tooth on pleonite 3 in L. dellavallei is dis-cussed. The validity of L. kinahani (Spence Bate, 1862) is questioned. An identification key is proposed for Mediterranean Liljeborgia species.